An Exploratory Study Of Malaysian Online Newspapers’ Representation Of Risks From Lynas Rare Earth Project - Dauda, Sharafa; Hasan, Nik Norma Nik (2015)
We propose a hybrid of the Social Amplification of Risk Framework and the Social Semiotic Theory of Multimodality to explore how discourses on risks from Lynas rare earth project in Malaysia are represented by Malaysian online newspapers. Evidence suggests that re-contextualizing voices in environmental reporting and framing reflect changes in relationship between stakeholders in Malaysia. There is also evidence of neglect of the plights of affected people and communities in environmental reporting in Malaysia’s mainstream print media. However, there is a dearth of evidence on how discourses by social actors on risks, especially on emerging technologies like rare earth in Malaysia are represented in Malaysian online newspapers. Yet the Malaysian online audience are active and enormous. In addition, Lynas’ rare earth project in Malaysia generated controversial discourses on the Internet, but not much is known about how these discourses were represented. Meanwhile, the Lynas plant in Kuantan got a two-year full operating license in 2014, already gulped over three billion Malaysian Ringgit, and stirred protests and heated debates at the highest levels amid allegations of inadequate long term plans for disposing radioactive toxic wastes which can have diverse risks. Supposedly, the fears draw from previous experiences from the Asian Rare Earth plant in Bukit Merah, Perak, which left radioactive wastes that caused workers and residents to suffer from leukemia, congenital diseases, lead poisoning and deaths. Statistically, the Kuantan plant produced 1,089 tonnes of rare earth oxides in the first quarter of 2014 and targets 11,000 tonnes yearly. This is 10 percent of global production in 2012. Therefore, this study proposes to explore types of risks represented, how the risks are defined and the relationship between the risks (if any). It also seeks to explore social actors who define, amplify or attenuate these risks; identify the modes used to convey meanings of the risks; and how the modes convey meanings of specific risks as represented in mainstream and alternative Malaysian online English language newspapers.